Avaliação de RAP1 como biomarcador das neoplasias cervicais: intraepitelial e invasora. - Paula Cristina de Vasconcelos Vieira (2019)
Cervical cancer is one of the most important causes of cancer-related deaths among women Worldwide, and Human Papillomavirus (HPV) infection is present in 99% of cases. In the last years, detection of pre-neoplastic lesion through the action of wellsucceeded programs of women’s screening, prevention and clinical follow-up has permitted the reduction of incidence of and mortality from cervical cancer in several countries. However, this neoplasia is still very prevalent. This issue has intensified the search for biological markers or Biomarkers that could improve the sensibility and specificity of programs of women’s screening. Among these BM is RAP1, a small GTPase with action in several cell signalizing pathways and neoplastic processes. However, our study evaluated in biopsies collected from the uterine cervix of women diagnosed by Histopathology as Cervicitis, Pre-neoplastic and Neoplastic lesions, (i) the RAP1 expression in lesioned areas of cervical epithelium by Immunohistochemistry methodology and; (ii) the prevalence of HPV infection by using a Nested-PCR protocol, and the HPV Genotyping by sequencing of a viral DNA fragment by using the Automatic DNA Sequencing technique. In this study, the presence of HPVDNA was observed in 72 (73.74%) out of the 99 cervical tissues samples, and HPV16 was the most commonly genotype found among the HPV-positive samples, especially in samples from the Cervical Intra-epithelial Neoplasia (CIN) grade III and Cervical cancer groups. Concerning the RAP1 expression in cervical tissues from distinct diagnosis, the protein Immuno-labeling was observed in tissue samples from the all analyzed groups. The labeling was predominantly in both sites nucleus and cytoplasm of epithelial cells, representing 69% of the total 90 tissue samples. In relation to the parameter “Labeling intensity”, it was verified that samples from the CIN III exhibited a higher intensity labeling for RAP1, than that observed in lesions of low-severity (CE + CINI). In the samples of Cervical cancer tissues, it is also possible to detect a labeling pattern of high intensity RAP1 staining, with strong nuclear labeling. It is noticed that in the most lesions of high-severity, CIN III and Cervical cancer the number of nuclear labeling is higher when compared to lesions of low-severity. In conclusion, our study highlights the potential use of RAP1 tissue labeling, as a biomarker for the detection of cervical lesions of high severity, and cervical cancer.